2021
DOI: 10.1007/s00414-021-02505-2
|View full text |Cite
|
Sign up to set email alerts
|

Forensic age estimation based on fast spin-echo proton density (FSE PD)–weighted MRI of the distal radial epiphysis

Abstract: Radiation exposure is a crucial factor to consider in forensic age estimation. The various magnetic resonance imaging (MRI) modalities used in forensic age estimation avoid radiation exposure. This study examined the reliability of distal radius ossification using fast spin-echo proton density (FSE PD)–weighted MRI to estimate age. Left wrist MRI findings of 532 patients aged 10–29 years were evaluated retrospectively using the five-stage system of Dedouit et al. The intra- and interobserver reliability values… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 39 publications
0
3
0
Order By: Relevance
“…They also retrospectively assessed the ossification degree of the distal femoral and proximal tibial epiphyses using a different MRI sequence-T1-weighted turbo spin echo (T1-TSE) MRI sequence. They found a significant correlation (p < 0.001) between age and ossification in these areas; however, again, the method was reliable only for people 14-17 years of age [34].…”
Section: Age Estimationmentioning
confidence: 92%
“…They also retrospectively assessed the ossification degree of the distal femoral and proximal tibial epiphyses using a different MRI sequence-T1-weighted turbo spin echo (T1-TSE) MRI sequence. They found a significant correlation (p < 0.001) between age and ossification in these areas; however, again, the method was reliable only for people 14-17 years of age [34].…”
Section: Age Estimationmentioning
confidence: 92%
“… 52 53 54 Dedouit classification and Saint-Martin classification have been used for most of the MRI-based bone age estimation where either ossification of radial and ulnar distal epiphysis or proximal humeral epiphysis was studied to determine the age of majority. 55 56 MRI knee joint has also been studied to evaluate the ossification center at distal femoral and proximal tibial epiphyses, either separately or in combination. These studies were based on either Dedouit or Schmeling–Kellinghaus classification systems.…”
Section: Limitations and Other Modalitiesmentioning
confidence: 99%
“…At present, resting-state functional MRI has been used in the research of PD pathology and has shown certain effects. MRI can locate in multiple directions and has high resolution for soft tissues, so that it is widely used for the diagnosis of many diseases clinically [ 11 , 12 ]. MRI would lead to fewer complications in stereotactic surgery, with less loss and a relatively simpler method [ 13 , 14 ].…”
Section: Introductionmentioning
confidence: 99%